Assessment of Integrity and Transparency in Operations of Mamungsongton Sub-District Administrative Organization, Mueang District, Nakhon Si Thammarat Province - Juntarakote, Benjaporn (Journal of Liberal Arts Prince of Songkla University, 2019)
The objectives of this research is to examine the integrity and transparency in the operation of the Mamungsongton sub-district administrative organization. Two methods were applied: 1) The document research by storing documents or other evidence according to the survey, using the empirical evidence (Evidence-Based Integrity and Transparency Assessment: EBIT) 2) The survey on Internal Integrity and Transparency Assessment (IIT) from a sample of 25 internal staff and the survey on External Integrity and Transparency Assessment (EIT) from a sample of 100 users in terms of the views, perceptions and experiences. The data was analyzed by using a statistical program. The weighted indexes are calculated. The results showed that the rate of integrity and transparency in the operations of the organization scored 76.57 percent, which is considered was high. Freedom from corruption index was the highest scoring 85.23 per cent which is very high. The accountability index showed 81.45 per cent which is very high level, followed by transparency index, integrity culture index and work integrity index showed a high level of 78.40, 69.12 and 65.09 per cent in respectively. Suggestions for improvement in the assessment in the future are the organization should provide training for knowledge and understanding to administrators and staff to realize the importance of evaluating the integrity and transparency in the operation at least once a year and the organization should promote anti-corruption campaigns for upcoming operations as well as raise staff’s awareness of all aspects of integrity and transparency.